2008
DOI: 10.1159/000176306
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Self-Reported Allergic Rhinitis in Eleven Major Cities in China

Abstract: Background: Allergic rhinitis (AR) is a common disease and its prevalence is increasing worldwide. Data on the current prevalence of AR in China, one of the biggest countries in the world, with a population of around 1.3 billion citizens, are scarce. The aim of this study was to investigate the prevalence of self-reported AR in Chinese citizens. Methods: In a cross-sectional, population-based study, telephone interviews were conducted in 11 major cities in China after sampling target telephone numbers through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
143
3
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 138 publications
(152 citation statements)
references
References 56 publications
5
143
3
1
Order By: Relevance
“…For Urumqi 13-14 years children, Chen et al [18] reported the prevalence of AR symptoms of 36.7%, just lower than that in Guangzhou (39.5%). A 2004 study in 11 Chinese cities conducted by telephone interview found Urumqi had the highest self-reported AR by 21.4% (age and gender adjusted) in the last 12 months, in which persistent AR, with higher symptom frequency and more severe symptoms, accounted for 36.1%, higher than the average 25.6% across the 11 cities [19]. It was argued that the Urumqi climate, which is arid, cold and windy, with a large temperature difference between day and night, is related with AR symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…For Urumqi 13-14 years children, Chen et al [18] reported the prevalence of AR symptoms of 36.7%, just lower than that in Guangzhou (39.5%). A 2004 study in 11 Chinese cities conducted by telephone interview found Urumqi had the highest self-reported AR by 21.4% (age and gender adjusted) in the last 12 months, in which persistent AR, with higher symptom frequency and more severe symptoms, accounted for 36.1%, higher than the average 25.6% across the 11 cities [19]. It was argued that the Urumqi climate, which is arid, cold and windy, with a large temperature difference between day and night, is related with AR symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…We do not have information on rhinitis in this study, but the prevalence of allergic rhinitis in the study area is about 10% [29]. Whether rhinitis mediates the 10 effect of MSG on SDB remains to be determined.…”
Section: Discussionmentioning
confidence: 91%
“…Allergy symptoms (e.g. sneezing, nasal congestion and itching) are collectively referred to as allergic rhinitis (AR) and has been reported in variable prevalence, such as 8%-24% self-report in China and in contrast 11%-30% self-report in the US (47,48). AR is an immunoglobulin E (IgE) mediated response, and can result in both localized or systemic inflammation (49).…”
Section: Aeroallergensmentioning
confidence: 99%